2016
DOI: 10.1007/s12678-016-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hypochlorite Reduction Related to the Sodium Chlorate Process

Abstract: Reduction of hypochlorite is the most important side reaction in the sodium chlorate reactor leading to high energy losses. Today chromate is added to the reactor solution to minimize the hypochlorite reduction but a replacement is necessary due to health and environmental risks with chromate. In order to understand the effect of different substrates on the hypochlorite reduction, α-FeOOH, γ-FeOOH, Cr 2 O 3 and CrOH 3 were electrodeposited on titanium and subjected to electrochemical investigations. These subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 50 publications
4
45
0
Order By: Relevance
“…The electrochemical and chemical reactions yielding chlorate have been well described in the literature [4][5][6][7][8][9][10][11]. The main half reactions are the cathodic reduction of water (Eq.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrochemical and chemical reactions yielding chlorate have been well described in the literature [4][5][6][7][8][9][10][11]. The main half reactions are the cathodic reduction of water (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to soluble molybdate, MoO 2 nanoparticles have been immobilized onto Ti and Fe electrodes in a Cr 2 O 3 matrix, yielding a surface very selective towards water reduction in the presence of hypochlorite [28]. However, it was shown elsewhere that electrodeposited Cr 2 O 3 completely prevents hypochlorite reduction on Ti electrodes [11] and, hence, the effects of MoO 2 particles as presented in [28] cannot be precisely evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3b. The addition of sodium dichromate provides selectivity towards water reduction by forming a chromium (III) oxide or hydroxide that effectively blocks the reduction of hypochlorite and chlorate [16]. In addition to current efficiency, there are also a change in physical appearance as a result of the formation of the chromium (III) film, i.e., the observable corrosion product and chromium (III) layer thickness.…”
Section: Process Performancementioning
confidence: 99%
“…The current efficiency has been studied in some publications, but the most common approach is to study the cell or electrode potential and oxygen production [9,10,[12][13][14][15][16][17]. It has also been reported that the time it takes to reach stable conditions in a chlorate cell or at the surface of a chlorate cathode is significantly long [8].…”
Section: Introductionmentioning
confidence: 99%